Electric guitar distortion effects unit using a Raspberry Pi - Pereira, Renato Santos; Andreão, Rodrigo Varejão (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2021)
With the advance of electronics, techniques and algorithms for digital signal processing, digital equipment has been gaining more and more space in the music scene. Micro-processed tools now generate several effects such as modulation, echo, and distortion of sounds generated by musical instruments, previously obtained only by analog units. In this context, this study aimed to develop aprototype of distortion effects unit using a Raspberry Pi (a low-cost small single-board computer) and affordable electronic components. Therefore, five nonlinear functionswere used, four of which are present in the literature andone of them was originally developed by the authors. These functions model the behavior of an active element (suchas transistors, valves, and operational amplifiers), which when they exceed their amplification thresholds produce distortions in the audio signals. Throughout this article, all the steps in the development of the analog circuits for signal acquisition and output will be presented, as well as the simulation and implementation of the functions in the microcontroller. At the end, with the finished prototype, the frequency response analysis is performed and the sound results achieved by the algorithms is compared with each other and with other distortion units.